Mechanism for Imposing Sanctions on Notaries Who Violate the Notary Code of Ethics: Mekanisme Pemberian Sanksi Terhadap Notaris yang Melakukan Pelanggaran Kode Etik Jabatan Notaris - M Arfan Gasali; Zulfika; Basrawi; Febriansyah, Rustam; Masyita, Siti; Nurlinda (Sangia Nibandera Law Research, 2024)
The notary code of ethics is the entire moral rules determined by the Indonesian Notary Association which applies to all members of the association and other people who hold and carry out the position of Notary both in the implementation of the position and in daily life. The notary code of ethics contains material elements regarding obligations, prohibitions, exceptions and sanctions that will be imposed on a notary who is proven to have violated the Code of Ethics, the Indonesian Notary Association (INI) as an organizational association for notaries has a very important role in enforcing the code of ethics. The Honorary Council is a tool of the association that is authorized to conduct investigations into violations of the code of ethics and impose sanctions on violators in accordance with its authority. A notary is a professional in the legal field who plays an important role in creating legal certainty and assisting the community in various civil legal matters. The implementation of sanctions imposed by the Honorary Council of the Indonesian Notary Association as a professional organization against Notaries who violate the code of ethics, are: reprimands, warnings and dismissal or dismissal from membership of the association. These sanctions only affect notaries as members of the association and do not affect notaries as public officials. To be a good legal professional in carrying out their professional duties in upholding the law, practitioners are required to possess qualified attitudes, a humanitarian attitude, an attitude of justice, the ability to see and place objective values ​​in a case they handle, an honest attitude, as well as technical skills and ethical maturity.